A cis‐eQTL genetic variant in PLK4 confers high risk of hepatocellular carcinoma. (6th September 2019) - Meng, Lijuan; Zhou, Yan; Ju, Sihan; Han, Jing; Song, Ci; Kong, Jing; Wu, Yifei; Lu, Shuai; Xu, Jiani; Yuan, Wenwen; Zhang, Erbao; Wang, Cheng; et al.
Abstract: Purpose: The overexpression and knockdown of PLK4 were both reported to generate aneuploidy. Thus, we aimed to investigate whether genetic variants in PLK4 contribute to the development of hepatocellular carcinoma (HCC). Methods: We evaluated associations of common variants in PLK4 and its promoter for the risk of HCC in our association study (1300 cases and 1344 controls). The genotype‐tissue expression (GTEx) and The cancer genome atlas (TCGA) databases were used to quantify the expression of PLK4 . Cell proliferation and migration affected by PLK4 in HCC were assessed in vitro. Drug susceptibility testing (DST) model was used to assess the sensibility of PLK4 ‐activated HCC to CFI‐400945, a small molecule inhibitor of PLK4. Results: Herein, we found a significant association between rs3811741, located in the PLK4 intron, and liver cancer risk (OR = 1.26, P  = 9.81 × 10 −5 ). Although PLK4 expressed at lower levels in somatic tissues compared to the testis, the risk allele A of rs3811741 was associated with increased PLK4 expression in liver cancer tissues. Additionally, PLK4 high expression was remarkably associated with shortened survival of HCC (HR = 1.97, P  = .001). Furthermore, overexpression of PLK4 promoted, while knockdown of PLK4 suppressed cancer cell proliferation, migration, and invasion. DST model demonstrated that CFI‐400945 can effectively suppress rampant proliferation of HCC with highly expressed PLK4 . Conclusion: Taken together, our study demonstrated that PLK4 is a susceptibility gene and plays an oncogenic role in HCC. Furthermore, we identified that PLK4 sensitives HCC to CFI‐400945, which may be an ideal therapy target for HCC. Abstract : PLK4 is a newly defined cancer‐testis gene. It's cis ‐eQTL genetic variant contributes to the development of hepatocellular carcinoma and sensitizes hepatocellular carcinoma (HCC) to CFI‐400945, which may be an ideal therapy target for HCC.